Composite modified slurry, modified ceramic-based composite membrane and preparation method

By using a composite modified slurry, a mixed slurry containing polyethylene oxide electrolyte film forming material, glacial acetic acid and LLZTO powder and a binder PVDF, the lithium battery separator is modified, and the problem of insufficient performance of the existing separator is solved and achieved Improved high thermal stability, mechanical properties and electrochemical properties.

CN115084779BActive Publication Date: 2025-02-07HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210666333.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-13
Publication Date
2025-02-07
Estimated Expiration
2042-06-13

AI Technical Summary

Technical Problem

The mechanical strength, thermal stability and electrochemical properties of existing lithium battery separators are insufficient, which affects the cycling performance, capacity retention and safety of the battery.

Method used

The separator is modified by a composite modified slurry containing polyethylene oxide electrolyte film forming material, a mixed slurry of glacial acetic acid and LLZTO powder and a binder PVDF, and the separator is modified by lifting method double-sided impregnation technology.

Benefits of technology

The thermal stability, mechanical properties, electrochemical properties and interface stability of the modified diaphragm are significantly improved, and the preparation method is simple, low-cost, environmentally friendly, and easy to mass production on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115084779B_ABST
    Figure CN115084779B_ABST
Patent Text Reader

Abstract

The invention relates to a composite modified slurry for modifying a battery separator, comprising: a polyethylene oxide electrolyte film-forming material, a mixed slurry of glacial acetic acid and LLZTO powder, and a binder PVDF; the polyethylene oxide electrolyte film-forming material is PEO-LiTFSI or PEO-LiFSI, and the molar ratio of PEO to Li is 6-10:1; in the mixed slurry of glacial acetic acid and LLZTO powder, the solvent is DMF, and the LLZTO powder is Li 6.75 LqCy 1.75 Ta 0.25 O 12 ; The amount of glacial acetic acid is 8-12% of the mass of LLZTO powder, and the amount of DMF is 8-12% of the mass of LLZTO powder; wherein the mass ratio of polyethylene oxide electrolyte film-forming material, LLZTO powder, and binder PVDF is 45-55:36-44:8-12. The base membrane to be modified, such as PE diaphragm or PP diaphragm, is double-sidedly impregnated with the composite modified slurry by the pulling method, then taken out and dried to obtain a modified diaphragm. It has been tested that the thermal stability, mechanical properties, electrochemical properties, interface stability and other properties of the modified diaphragm are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy batteries, and in particular to a composite modified slurry for modifying battery separators, a modified ceramic-based composite membrane and a preparation method thereof. Background Art

[0002] In the structure of lithium batteries, the diaphragm is one of the key inner components. The main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. The performance of the diaphragm determines the interface structure and internal resistance of the battery, which directly affects the battery's capacity, cycle and safety performance. The diaphragm with excellent performance plays an important role in improving the comprehensive performance of the battery. Different types of batteries use different diaphragms. The commercialized diaphragm materials are mainly polyethylene (PE) and polypropylene (polyacryl, PP) based polyolefin (Polyylene) diaphragms. However, the mechanical strength (especially tensile strength) and thermal stability of pure PE or PP diaphragms are poor, which limits the ambient temperature suitable for their application. At the same time, the mechanical strength of pure PE or PP diaphragms is poor. After multiple cycles of the battery, lithium dendrites are easily formed on the surface, resulting in puncture holes in the diaphragm. These factors seriously affect the battery's cycle performance, cycle capacity retention rate and battery safety.

[0003] In order to improve the performance of pure PE or PP diaphragms, many technical reports on PE or PP + ceramic coating diaphragm materials have appeared today, that is, the PE or PP diaphragms are modified by using the high temperature resistance and high mechanical strength of the ceramic coating. For example, Hu Xuyao, Shang Yuming and others published an article entitled "Nano-silicon dioxide / polyimide coating modified polypropylene diaphragm" in 2013, which disclosed the use of SiO2 inert filler to modify the PP diaphragm, and the tightly packed SiO2 nanoparticles overlapped each other on the membrane surface to form a rigid support layer, so that the modified PP diaphragm has good heat shrinkage resistance, but it is not clear whether the tensile strength of the modified diaphragm is significantly improved. The specification of CN110459803A records that the inorganic ceramic electrolyte LLZTO, the polymer electrolyte modified PEO and the PPO copolymer, the lithium salt LiCLO4 and acetonitrile are mixed to obtain an organic-inorganic electrolyte slurry. The organic-inorganic electrolyte slurry is filled into the composite substrate by repeated pressure casting and repeated drying. The organic-inorganic electrolyte slurry is filled in the pores of the composite substrate. After hot pressing, a modified composite electrolyte membrane with a density of 95% is obtained. It is measured that the composite electrolyte membrane has a density of 1.5*10 -4This solution is not only complicated to operate, but also requires repeated pressure casting, repeated drying and hot pressing to fill the PE diaphragm substrate. The LLZTO introduced in this way has poor adhesion to the surface of the base film and is easy to fall off from the pole piece during long-term operation of the battery. At the same time, the ionic conductivity of the composite electrolyte membrane is low. When used for solid electrolyte membrane, the internal resistance is large, the rate performance is generally low, and the voltage drop is large during high-rate discharge.

[0004] In summary, there are still many deficiencies in the performance of existing diaphragms, and it is necessary to propose improvement plans to improve the performance of existing diaphragms or composite electrolyte membranes. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a composite modified slurry for modifying a battery separator, a modified ceramic-based composite membrane and a preparation method thereof, wherein the composite membrane has high thermal stability, high ionic conductivity and excellent mechanical strength, and has good interface stability with the electrode. In addition, the preparation method provided by the present invention has the advantages of simple operation method, low cost, environmental protection, good repeatability, and easy large-scale batch production.

[0007] (II) Technical solution

[0008] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0009] In a first aspect, the present invention provides a composite modified slurry for modifying a battery separator, which contains: a polyethylene oxide electrolyte film-forming material, a mixed slurry of glacial acetic acid and LLZTO powder, and a binder PVDF;

[0010] Wherein, the polyethylene oxide electrolyte film-forming material is PEO-LiTFSI or PEO-LiFSI, and the molar ratio of PEO to Li is 6-10:1;

[0011] In the mixed slurry of glacial acetic acid and LLZTO powder, the solvent is DMF and the LLZTO powder is Li 6.75 Ln3Z 1.75 Ta 0.25 O 12 ; Glacial acetic acid is 8-12% of the mass of LLZTO powder, and DMF is 8-12% of the mass of LLZTO powder;

[0012] Among them, the mass ratio of polyethylene oxide electrolyte film-forming material, LLZTO powder and binder PVDF is 45-55:36-44:8-12.

[0013] Preferably, the polyethylene oxide electrolyte film-forming material is PEO-LiTFSI, and the molar ratio of PEO to Li is 8:1.

[0014] Preferably, in the mixed slurry of glacial acetic acid and LLZTO powder, the amount of glacial acetic acid is 10% of the mass of the LLZTO powder, and the amount of DMF is 10% of the mass of the LLZTO powder.

[0015] Preferably, in the composite modified slurry, the mass ratio of the polyethylene oxide electrolyte film-forming material, the LLZTO powder and the binder PVDF is 50:40:10.

[0016] The base film to be modified, such as PE diaphragm or PP diaphragm, is dipped into the composite modified slurry on both sides by the pulling method, then taken out and dried to obtain the modified diaphragm. The thermal stability, mechanical properties, electrochemical properties, interface stability and other properties of the modified diaphragm are significantly improved.

[0017] In a second aspect, the present invention provides a method for preparing a modified ceramic-based composite membrane, comprising the following steps:

[0018] S1. Prepare a powder of lithium-containing conductive ceramic LLZTO; prepare a polyethylene oxide electrolyte film-forming material, wherein the polyethylene oxide electrolyte film-forming material is PEO-LiTFSI or PEO-LiFSI, and the molar ratio of PEO to Li is 6-10:1;

[0019] S2, adding 8-12% of glacial acetic acid and 8-12% of DMF by weight of the lithium-containing conductive ceramic LLZTO powder to the lithium-containing conductive ceramic powder, and mixing and stirring to obtain a mixed slurry of glacial acetic acid and LLZTO;

[0020] S3, mixing polyethylene oxide electrolyte film-forming material, a mixed slurry of glacial acetic acid and LLZTO, and a binder PVDF, adding a powder dispersant, and fully stirring to obtain a composite modified slurry; in the composite modified slurry, the mass ratio of polyethylene oxide electrolyte film-forming material, LLZTO powder, and PVDF is 45-55:36-44:8-12;

[0021] S4. The front and back sides of the base membrane to be modified are immersed in the composite modification slurry by using a pulling method, and then dried to obtain a modified ceramic-based composite membrane.

[0022] According to a preferred embodiment of the present invention, in S1, the chemical formula of the lithium-containing conductive ceramic LLZTO is Li 7-x Ln3Z 2- x Ta x O 12 ; Among them, 0 <x<1。

[0023] According to a preferred embodiment of the present invention, in S1, LLZTO is Li 6.75 Ln3Z 1.75 Ta 0.25 O 12 or Li 6.6 Ln3Z 1.6 Ta 0.4 O 12 More preferably, Li 6.75 Ln3Z 1.75 Ta 0.25 O 12 When x=0.25, the modification effect of the conductive ceramic LLZTO on the PE-based film or the PP-based film is the best.

[0024] According to a preferred embodiment of the present invention, in S1, in the polyethylene oxide electrolyte film-forming material, the molar ratio of PEO to Li is 8:1.

[0025] PEO and LiTFSI or LiFSI are weighed respectively according to a predetermined molar ratio and then mixed evenly to prepare a polyethylene oxide electrolyte film-forming material.

[0026] According to a preferred embodiment of the present invention, in S2, 10% of glacial acetic acid and 10% of DMF, which account for 10% of the mass of the lithium-containing conductive ceramic powder, are added to the lithium-containing conductive ceramic LLZTO powder.

[0027] According to a preferred embodiment of the present invention, in S3, in the composite modified slurry, the mass ratio of polyethylene oxide electrolyte film-forming material, LLZTO powder, and PVDF is 50:40:10. When the ratio of the three materials is 50:40:10, the composite modified slurry has the best modification effect on the PE base film or PP base film, the electrochemical performance of the diaphragm is optimal, and the conductive ceramic LLZTO can be firmly bonded to the base film, so that the modified membrane and the electrode have good interface stability. In addition, experiments have also confirmed that the composite modified slurry that meets this ratio can enable the modified diaphragm to obtain the best mechanical properties and thermal stability.

[0028] According to a preferred embodiment of the present invention, in S3, the powder dispersant is Auda powder dispersant AD8085.

[0029] By adding a powder dispersant (such as Auda powder dispersant AD8085), the electrostatic repulsion generated after adsorption on small particles disperses the particles, making the prepared slurry disperse more quickly, avoiding the agglomeration of LLZTO, and effectively shortening the stirring time of the slurry. Compared with the case without adding powder dispersant, the stirring time can be shortened by half.

[0030] According to a preferred embodiment of the present invention, in S4, the base film to be modified is a PE base film, the number of immersions is 3 times, and the drying conditions are 75-85°C for 10-15 hours.

[0031] In a third aspect, the present invention provides a modified ceramic-based composite membrane, which is prepared by the preparation method of any of the above embodiments.

[0032] (III) Beneficial effects

[0033] The beneficial effects of the present invention are:

[0034] (1) The present invention uses inorganic conductive ceramic LLZTO to modify PE or PP diaphragms, which can more effectively improve the mechanical strength and thermal stability of the modified diaphragms; when the base film is PE, the present invention uses inorganic conductive ceramic LLZTO to improve the tensile strength of the diaphragm more significantly than SiO2 modified PE diaphragms. 7-x LqCy 2-x Ta x O 12 ) takes 0.25, the modification effect is most prominent. Due to the doping of metal element Ta in LLZTO, LLZTO can form a stable cubic phase. Under the same conditions, the conductivity of PE diaphragm modified by LLZTO is about 2 times higher than that of LLZO with tetragonal structure.

[0035] Usually, unmodified PE separators have a lower melting point (140℃-150℃). LLZTO has higher thermal stability (its own high temperature resistance is above 600℃). Adding LLZTO to PE separators can improve the thermal stability of PE separators, which plays a vital role in the safety of batteries.

[0036] (2) Without the addition of PVDF, LLZTO has poor adhesion to the surface of the base film and is prone to fall off from the pole piece during long-term operation of the battery. The present invention introduces the binder PVDF, which can greatly increase the viscosity of the composite modified slurry, so that LLZTO can be firmly bonded to the PE / PP base film, thereby improving the interfacial stability between the modified diaphragm and the electrode. In addition, PVDF can also effectively prevent the crystallization of PEO in the polyethylene oxide electrolyte film-forming material and improve the electrochemical properties of the modified PE diaphragm. In the prior art, PEO-LiTFSI (or together with inorganic conductive ceramics) is used as a modified material for the diaphragm, but the crystallization of PEO causes the ionic conductivity of the diaphragm to be poor. In the present invention, a certain amount of PVDF is added to the composite modified slurry, and PVDF will be dispersed in the PEO (polyethylene oxide) heterogeneous system, thereby inhibiting the crystallization of PEO-LiTFSI and improving the electrochemical properties of the modified PE diaphragm. The combination of inorganic conductive ceramic LLZTO and adhesive PVDF can effectively improve the mechanical properties and thermal stability of PE separators.

[0037] (3) In the preparation method of the present invention, glacial acetic acid accounting for about 10% of the mass of the lithium-containing conductive ceramic LLZTO powder is added to the lithium-containing conductive ceramic powder, and the technical effects thereof include:

[0038] ① Reduce the alkalinity of the LLZTO and DMF mixed system in advance to prevent the subsequent addition of PVDF from decomposing in a highly alkaline environment, effectively inhibit the alkaline decomposition effect of PVDF, make PVDF and LLZTO have better compatibility, and contribute to the formation of the Lewis acid-base effect between PVDF and LLZTO, and improve the electrochemical performance of the composite modified slurry system. LLZTO and DMF are easily mixed to form a highly alkaline environment, so the addition of glacial acetic acid in the present invention can reduce the alkalinity, prevent PVDF from alkaline decomposition, and prevent the inability to construct an ideal composite modified slurry system due to PVDF decomposition. ② In addition, LLZTO is very sensitive to moisture. When exposed to the atmospheric environment, it will react with water molecules to generate LiOH, and LiOH will react with carbon dioxide to generate Li2CO3. The presence of Li2CO3 will inhibit the formation of a highly conductive layer, reduce the electropositivity of LLZTO particles, and weaken its synergistic effect with the lithium salt in PEO-LiTFSI. However, the prior art does not remove the Li2CO3 impurities therein, and some disclosed technologies require the preparation and preservation of modified composite slurries in an argon atmosphere or a glove box, which is very unfavorable for industrial applications. In the present invention, glacial acetic acid and DMF are added to LLZTO, and DMF is used to isolate moisture and air. Glacial acetic acid can remove Li2CO3 impurities, purify LLZTO, enhance the synergistic effect of LLZTO and the lithium salt in PEO-LiTFSI, and promote the formation of a highly conductive layer. Glacial acetic acid is a weak acid and does not have strong oxidizing properties, and will not have adverse effects on the PE base film. Glacial acetic acid cannot be replaced by other oxidizing acids. ③ The carboxyl group of glacial acetic acid in the composite modified slurry can also provide additional transmission channels for the transport of lithium ions, thereby increasing the ionic conductivity and electrochemical properties of the modified slurry and the modified diaphragm.

[0039] In summary, LLZTO, PEO-LiTFSI, PVDF and glacial acetic acid in the composite modified slurry prepared by the present invention achieve a synergistic effect on the modification function of the diaphragm, thereby obtaining a modified diaphragm with good mechanical properties and thermal stability, excellent tensile strength, high ionic conductivity, and good interface stability between electrodes; and compared with the modification method of the prior art of repeatedly pressurizing and pouring, repeatedly drying and hot pressing to fill the PE diaphragm, the preparation method of the present invention is only for batching, stirring and mixing, and dipping and pulling, and the operation method is very simple. The entire preparation process does not need to be carried out in argon or a glove box. The preparation process of the composite modified slurry has no strict requirements on the environment, and no special special production equipment is required, so it is very convenient for industrial application. The composite modified slurry of the special formula ingredients of the present invention, while enhancing a series of properties of the PE diaphragm, also has the advantages of adjustable film thickness, low cost, environmental protection, good repeatability, and easy batch production. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1This is the SEM image of the cubic phase LLZTO prepared in Example 1 of the present invention.

[0041] Figure 2 This is the SEM image of the modified PE diaphragm prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0043] Example 1

[0044] This embodiment provides a method for preparing a modified ceramic-based composite membrane, the steps are as follows:

[0045] (1) preparing powder of lithium-containing conductive ceramic LLZTO;

[0046] 2.83g LiOH·H2O, 2.15g ZrO2, 9.77g La2O3, and 1.1g Ta2O5 were placed in a zirconia ball mill, 50ml isopropanol was added, and the zirconia ball was used for ball milling at 250rpm for 6 hours. The obtained slurry was dried in a forced air drying oven at 80°C for 12 hours. The obtained powder was calcined in a muffle furnace at 950°C for 12 hours using an alumina ark. The powder was then calcined in an air environment at 1150°C for 14 hours using a tube furnace, and ball milled again for 6 hours to obtain Li 7-x LqCy 2-x Ta x O 12 White powder, denoted as LLZTO, where x = 0.25. The SEM image of the prepared cubic phase LLZTO is shown in Figure 1 shown.

[0047] (2) PEO and LiTFSI were weighed according to a molar ratio of PEO:Li=8:1, and stirred and mixed for 2 hours to prepare a polyethylene oxide electrolyte film-forming material, which was recorded as PEO-LiTFSI.

[0048] (3) LLZTO powder was mixed with 10 wt % DMF and 10 wt % glacial acetic acid and stirred for 2 h to obtain a mixed slurry of glacial acetic acid and LLZTO, recorded as LLZTO-10% glacial acetic acid; glacial acetic acid was used to reduce the alkalinity of the mixed slurry.

[0049] (4) 50 parts by weight of PEO-LiTFSI, LLZTO-10% glacial acetic acid (including 40 parts by weight of LLZTO powder), and 10 parts by weight of PVDF were mixed, and 1 wt% of the total amount of the mixture was added with an Auda powder dispersant AD8085 and stirred for 12 hours to obtain a composite modified slurry, recorded as 50[PEO-LiTFSI]-40[LLZTO]-10PVDF+10% glacial acetic acid.

[0050] (5) The front and back sides of a pure PE film (commercially available product) were immersed in the composite modified slurry three times by the pulling method, and then dried at 80°C for 12 h to obtain a modified PE film.

[0051] The SEM image of the modified PE diaphragm is shown in Figure 2 As shown, it can be seen that a large amount of nano-conductive ceramic LLZTO powder is attached to the surface of the base film. The modified PE diaphragm was subjected to a breakdown voltage test, and its breakdown voltage was 1.69KV; the tensile strength was 25.3MPa, the thickness was 20μm, and it also had excellent thermal stability: the surface would not shrink or melt after being kept at 150°C for 2h. The modified PE diaphragm was subjected to a tensile test and left to stand for 10 minutes under the pressure of a 300g weight. The modified PE diaphragm did not break or undergo obvious deformation, indicating that the diaphragm has good mechanical properties. The ionic conductivity was tested to be approximately 3.4*10 -4 S / cm.

[0052] Example 2

[0053] The difference between this embodiment and embodiment 1 is that in step (1), the molar ratio of LiOH·H2O, ZrO2, La2O3 and Ta2O5 is adjusted to obtain Li 7-x Ln3Z 2-x Ta x O 12 White powder, wherein x = 0.4. The remaining steps and conditions are the same as those in Example 1.

[0054] Example 3

[0055] The difference between this embodiment and embodiment 1 is that in step (2), the molar ratio of PEO:Li=10:1 is adjusted, PEO and LiTFSI are weighed, and stirred and mixed to obtain a polyethylene oxide electrolyte film-forming material, which is recorded as PEO-LiTFSI.

[0056] Example 4

[0057] The difference between this embodiment and embodiment 1 is that in step (2), the molar ratio of PEO:Li=6:1 is adjusted, PEO and LiTFSI are weighed, and stirred and mixed to obtain a polyethylene oxide electrolyte film-forming material, which is recorded as PEO-LiTFSI.

[0058] Example 5

[0059] The difference between this embodiment and embodiment 1 is that in step (3), the addition amounts of DMF and glacial acetic acid are adjusted to 8 wt % of the conductive ceramic LLZTO powder to obtain a mixed slurry of glacial acetic acid and LLZTO, which is recorded as LLZTO-8% glacial acetic acid.

[0060] Example 6

[0061] The difference between this embodiment and embodiment 1 is that in step (3), the addition amounts of DMF and glacial acetic acid are adjusted to 12 wt % of the conductive ceramic LLZTO powder to obtain a mixed slurry of glacial acetic acid and LLZTO, which is recorded as LLZTO-12% glacial acetic acid.

[0062] Example 7

[0063] The difference between this embodiment and embodiment 1 is that in step (4), the mixing ratio of PEO-LiTFSI, LLZTO-10% glacial acetic acid and PVDF is adjusted so that the mixing mass ratio of PEO-LiTFSI, LLZTO powder and PVDF is 45:45:10. Similarly, 1wt% of Auda powder dispersant AD8085 is added and stirred for 12 hours to obtain a composite modified slurry, which is recorded as 45[PEO-LiTFSI]-45[LLZTO]-10PVDF+10% glacial acetic acid.

[0064] Example 8

[0065] The difference between this embodiment and embodiment 1 is that in step (4), the mixing ratio of PEO-LiTFSI, LLZTO-10% glacial acetic acid and PVDF is adjusted so that the mixing mass ratio of PEO-LiTFSI, LLZTO powder and PVDF is 54:36:10. Similarly, 1 wt% of Auda powder dispersant AD8085 is added and stirred for 12 hours to obtain a composite modified slurry, which is recorded as 54[PEO-LiTFSI]-36[LLZTO]-10PVDF+10% glacial acetic acid.

[0066] Example 9

[0067] The difference between this embodiment and embodiment 1 is that in step (4), the mixing ratio of PEO-LiTFSI, LLZTO-10% glacial acetic acid and PVDF is adjusted so that the mixing mass ratio of PEO-LiTFSI, LLZTO powder and PVDF is 48:40:12. Similarly, 1wt% of Auda powder dispersant AD8085 is added and stirred for 12 hours to obtain a composite modified slurry, which is recorded as 48[PEO-LiTFSI]-40[LLZTO]-12PVDF+10% glacial acetic acid.

[0068] Example 10

[0069] The difference between this embodiment and embodiment 1 is that in step (4), the mixing ratio of PEO-LiTFSI, LLZTO-10% glacial acetic acid, and PVDF is adjusted so that the mixing mass ratio of PEO-LiTFSI, LLZTO powder, and PVDF is 55:36:9. Similarly, 1 wt% of Auda powder dispersant AD8085 is added and stirred for 12 hours to obtain a composite modified slurry, which is recorded as 55[PEO-LiTFSI]-36[LLZTO]-9PVDF+10% glacial acetic acid.

[0070] The modified PE separators prepared in Examples 2-10 were tested for various properties such as breakdown voltage, tensile strength, thickness, thermal stability, tensile test, and ionic conductivity. The results are shown in Table 1:

[0071] Table 1

[0072]

[0073]

[0074] Note: Thermal stability is to keep the temperature at 150℃ for 2h and observe whether the surface shrinks / melts. The tensile test is to fix one end of the modified PE diaphragm on the bracket with a clip and connect a 300g weight to the other end and let it stand for 10min to observe whether the modified PE diaphragm breaks and deforms.

[0075] The following is combined with comparative examples to further illustrate the significant technical effects of the scheme of the present invention.

[0076] Comparative Example 1

[0077] This comparative example is a commercially available PE diaphragm product before modification.

[0078] Comparative Example 2

[0079] This comparative example uses PI (polyimide) as a binder and nano-SiO2 to modify the pure PE diaphragm. The modification method is: 0.25g of soluble PI is dissolved in NMP, 2.25g of nano-SiO2 (particle size 30-50nm) is added, stirred for 1h, and ultrasonically dispersed for 30min to prepare a modified coating solution. The coating solution is applied to the surface of both sides of the PE diaphragm to fully infiltrate, and the NMP is vacuum dried at 60 degrees Celsius to obtain a modified composite membrane.

[0080] Comparative Example 3

[0081] This comparative example is based on Example 1, and the LLZTO used is replaced by LLZO without Ta doping, namely Li7La3Zr2O 12 The other steps and conditions are the same as those in Example 1.

[0082] Comparative Example 4

[0083] This comparative example is based on Example 1, except that the PVDF used is replaced by an equal amount of PI.

[0084] Comparative Example 5

[0085] This comparative example is based on Example 1, except that PVDF is not added in step (4), and the composite modified slurry is 50[PEO-LiTFSI]-50[LLZTO]+10% glacial acetic acid. Other steps and conditions are the same as those in Example 1.

[0086] Comparative Example 6

[0087] This comparative example is based on Example 1, except that the glacial acetic acid used in step (3) is removed. The other steps and conditions are the same as those in Example 1.

[0088] The modified PE diaphragms prepared in Comparative Examples 1-6 were tested for various properties such as breakdown voltage, tensile strength, thermal stability, tensile test, and ionic conductivity. The results are shown in Table 2:

[0089] Table 2

[0090] Group Breakdown voltage Thermal stability Tensile test tensile strength Ionic conductivity Example 1 1.69KV No shrinkage / melting No breakage / deformation 25.3MPa <![CDATA[3.4*10 -4 S / cm]]> Comparative Example 1 1.00KV Obvious shrinkage and melting There is obvious deformation 12MPa <![CDATA[1.3*10 -4 S / cm]]> Comparative Example 2 1.58KV No shrinkage / melting There is some deformation 14.2MPa <![CDATA[2.0*10 -4 S / cm]]> Comparative Example 3 1.56KV No shrinkage / melting No breakage / deformation 21.3MPa <![CDATA[1.5*10 -4 S / cm]]> Comparative Example 4 1.60KV No shrinkage / melting No breakage / deformation 22.6MPa <![CDATA[2.1*10 -4 S / cm]]> Comparative Example 5 1.43KV Slightly wrinkled No breakage / deformation 15.8MPa <![CDATA[1.4*10 -4 S / cm]]> Comparative Example 6 1.50KV No shrinkage / melting No breakage / deformation 22.7MPa <![CDATA[1.8*10 -4 S / cm]]>

[0091] In summary, by comparing Example 1 with Comparative Example 1, it can be seen that the modified PE membrane prepared by the present invention is significantly improved in terms of anti-puncture ability, thermal stability, tensile performance, ionic conductivity, etc. compared with the pure PE film before modification, and a new PE membrane with excellent comprehensive performance is obtained. By comparing Example 1 with Comparative Example 2, the modification method of the present invention is compared with the inorganic nano-SiO2-PI modification method, and the PE membrane prepared by the present invention is significantly improved in terms of ionic conductivity and tensile strength. By comparing Example 1 with Comparative Example 3, the present invention uses Ta-doped LLZTO, which enables it to stably form a cubic phase, and the ionic conductivity is higher than that of the LLZO-modified PE membrane under the same conditions; in addition, LLZTO modification enables the PE membrane to have good interface stability. It can be seen from Example 1 compared with Comparative Examples 4 and 5 that PVDF can be better dispersed in PEO to effectively prevent PEO crystallization to obtain higher ionic conductivity, and PVDF can effectively increase the adhesion of the conductive ceramic LLZTO, thereby stabilizing the interface between the PE diaphragm and the electrode. The adhesion of LLZTO is greater and is conducive to obtaining higher thermal stability and tensile strength. Compared with Example 1, the PE diaphragm prepared in the absence of PVDF has a significant decrease in ionic conductivity and poor interface stability. This is mainly because the PE film is modified by PEO-LiTFSI and LLZTO alone, and the adhesion of LLZTO powder is poor, so the thermal stability and conductivity modification of LLZTO are not obvious, and PEO crystallization also reduces ionic conductivity. It can be seen from the comparison between Example 1 and Comparative Example 6 that after removing glacial acetic acid in the preparation method, the ionic conductivity of the modified PE membrane decreases. This is mainly due to the alkaline decomposition of PVDF in the strong alkaline mixed system of LLZTO and DMF, and the negative impact caused by the inevitable small amount of Li2CO3 impurities in LLZTO.

[0092] In summary, LLZTO, PEO-LiTFSI, PVDF and glacial acetic acid in the composite modified slurry prepared by the present invention achieve a synergistic effect in the modification function of the diaphragm, thereby obtaining a modified diaphragm with good mechanical properties and thermal stability, excellent tensile strength, high ionic conductivity, and good interface stability with the electrode.

[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for modifying a battery separator, characterized in that: It includes the following steps: S1. Prepare a powder of lithium-containing conductive ceramic LLZTO; prepare a polyethylene oxide electrolyte film-forming material, wherein the polyethylene oxide electrolyte film-forming material is PEO-LiTFSI or PEO-LiFSI, and the molar ratio of PEO to Li is 6-10:1; S2, adding 8-12% of glacial acetic acid and 8-12% of DMF by weight of the lithium-containing conductive ceramic LLZTO powder to the lithium-containing conductive ceramic powder, and mixing and stirring to obtain a mixed slurry of glacial acetic acid and LLZTO; S3, mixing polyethylene oxide electrolyte film-forming material, a mixed slurry of glacial acetic acid and LLZTO, and a binder PVDF, adding a powder dispersant, and fully stirring to obtain a composite modified slurry; in the composite modified slurry, the mass ratio of polyethylene oxide electrolyte film-forming material, LLZTO powder, and PVDF is 45-55:36-44:8-12; S4, immersing the front and back sides of the base film to be modified in the composite modification slurry by a pulling method, and drying to obtain a modified ceramic-based composite membrane; The base film to be modified is a PE or PP battery separator.

2. The modification method according to claim 1, characterized in that: In S1, the chemical formula of lithium-containing conductive ceramic LLZTO is Li 7-x Ln3Z 2-x Ta x O 12 ; Among them, 0 <x<1。 3. The modification method according to claim 1, characterized in that: In S1, the lithium-containing conductive ceramic LLZTO is Li 6.75 Ln3Z 1.75 Ta 0.25 O 12 .

4. The modification method according to claim 1, characterized in that: In S1, in the polyethylene oxide electrolyte film-forming material, the molar ratio of PEO to Li is 8:

1.

5. The modification method according to claim 1, characterized in that: In S2, 10% of glacial acetic acid and 10% of DMF, which account for 10% of the mass of the lithium-containing conductive ceramic powder, are added to the lithium-containing conductive ceramic LLZTO powder.

6. The modification method according to claim 1, characterized in that: In S3, in the composite modified slurry, the mass ratio of polyethylene oxide electrolyte film-forming material, LLZTO powder and PVDF is 50:40:

10.

7. The modification method according to claim 2, characterized in that: In S3, the powder dispersant is Auda powder dispersant AD8085.

8. The modification method according to claim 1, characterized in that: In S4, the base film to be modified is a PE base film, and the number of immersions is 3 times; the drying condition is 75-85° C. for 10-15 hours.

9. A modified ceramic-based battery separator, characterized in that: The battery separator is prepared by the modification method of any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composite electrolyte membrane and preparation method and application thereof

    CN110459803A

  • Solid-state lithium ion battery and preparation method thereof

    CN114583246A